Systematic Data Collection on and Status of Thai Industrial Tuna Purse Seine Operations in the Indian Ocean - Praulai Nootmorn; Saran Petpiroon; Kanokwan Maeroh (Agriculture and Natural Resources, 2010)
Six Thai industrial tuna purse sein fishing vessels operated in the Indian Ocean from 2005 to 2006. Fishery information and logistical data were gathered from log books, port sampling and interviews to create a systematic diagram of data collection and processing. The results will be used to support and implement responsible fishery operations under a resolution of the Indian Ocean Tuna Commission. The total catch reported was 12,216 metric tonne (tonne) in 2005 and 23,161 tonne in 2006, with the main fishing ground being off Somalia and the main fishing practice was with associated schools. The highest values for catch data, catch per unit effort (CPUE) and the number of sets were obtained during February to April and September to November in 2006. The monthly catch, CPUE and number of sets ranged from 383-4539 tonne, 15 to 61 tonne/set and 15 to 144 sets, respectively. Skipjack tuna was the main target fish, followed by bigeye tuna, yellowfin tuna and bonito. Skipjack tuna made up a high proportion of the catch during March to September, while bigeye and yellowfin tuna made up a high proportion from September to December 2005 and from January to February in 2006. The size range of skipjack, bigeye and yellowfin tuna varied from 39-75, 45-133 and 33-152 cm, respectively, whilst the length of 50% of capture fish was 60, 66 and 81 cm, respectively. Most of the bigeye and yellowfin tuna were juvenile. The status of bigeye tuna from tuna purse seine fishing was stable in terms of catch and CPUE.